Retrospective evaluation of the use of autologous blood‐patch treatment for persistent pneumothorax in 8 dogs (2009–2012). (16th April 2014) - Oppenheimer, Nama; Klainbart, Sigal; Merbl, Yael; Bruchim, Yaron; Milgram, Josh; Kelmer, Efrat
Abstract: Objective: To describe the clinical course, outcome and success rate of 8 dogs with persistent pneumothorax treated with autologous blood‐patch pleurodesis (ABP). Design: Retrospective case series. Setting: University teaching hospital Animals: Eight client‐owned dogs. Intervention: Non‐coagulated blood was aseptically collected from the jugular vein and injected immediately into the pleural cavity of dogs with persistent pneumothorax. Measurements and Main Results: The procedure was successful in 7 of 8 dogs. The median duration of pneumothorax until the ABP was performed was 4 days (range 2–6 days). Pneumothorax resolved immediately after 1 treatment in 4 dogs. Pleurodesis was repeated once in 3 dogs, and twice in 1 case after which it resolved in 3 of the 4 dogs. Out of a total of 13 ABP procedures performed in 8 dogs, 5 (62.5%) were successful after 1 procedure and the success rate increased to 87.5% after additional procedures. One dog failed ABP and was euthanized 3 days later due to continued deterioration and a hospital acquired pneumonia. Mild to moderate complications occurred in 2 other dogs and resolved in both. Conclusions: ABP is a simple, inexpensive, and relatively safe procedure which can be considered in dogs with persistent pneumothorax that have failed conservative or surgical management. Infections following ABP were documented in 2 of the 8 dogs and resolved in 1 dog.